2010
DOI: 10.1016/j.bbrc.2010.06.077
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of the rat cardiac sphingolipid pool in two mitochondrial subpopulations

Abstract: Mitochondrial sphingolipids play a diverse role in normal cardiac function and diseases, yet a precise quantification of cardiac mitochondrial sphingolipids has never been performed. Therefore, rat heart interfibrillary (IFM) and subsarcolemmal (SSM) mitochondria were isolated, lipids extracted, and sphingolipids quantified by LC-tandem mass spectrometry. Results showed that sphingomyelin (~10,000 pmols/mg protein) was the predominant sphingolipid regardless of mitochondrial subpopulation, and measurable amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
(43 reference statements)
2
18
0
1
Order By: Relevance
“…In addition, biochemical composition of the two cristae structures may differ in terms of lipid or protein contents, which could ultimately influence structure (108). Indeed, examination of the sphingolipid pool in cardiac SSM and IFM has revealed differences in the content of ceramide, which was higher in the SSM (88).…”
Section: Structural and Functional Differencesmentioning
confidence: 99%
“…In addition, biochemical composition of the two cristae structures may differ in terms of lipid or protein contents, which could ultimately influence structure (108). Indeed, examination of the sphingolipid pool in cardiac SSM and IFM has revealed differences in the content of ceramide, which was higher in the SSM (88).…”
Section: Structural and Functional Differencesmentioning
confidence: 99%
“…LC was carried out using a Shimadzu high-pressure LC system (Columbia, MD) with LC elution conditions as described previously ( 18 ). The system was coupled to an Applied Biosystems API 3000 triple quadrupole mass spectrometer with a TurboIon spray source operated with both mass analyzers set at unit resolution in positive mode (LC-MS/MS, Applied Biosystems/MDS Sciex API 3000, Foster City, CA).…”
Section: Brain Tissue Extraction For Dha-pc Analysis By Triple Quadrumentioning
confidence: 99%
“…Despite being present in the same cell, SSM and IFM have different respiration rates, metabolic enzyme activities, cristae structure and lipid content [31,34,38,42], and are exposed to different subcellular environments. In recent years it has been shown that the two populations have different susceptibilities to damage in disease [11,27].…”
Section: Introductionmentioning
confidence: 99%